2022
DOI: 10.1186/s12974-022-02428-8
|View full text |Cite
|
Sign up to set email alerts
|

Homer1 promotes the conversion of A1 astrocytes to A2 astrocytes and improves the recovery of transgenic mice after intracerebral hemorrhage

Abstract: Background Inflammation induced by intracerebral hemorrhage (ICH) is one of the main causes of the high mortality and poor prognosis of patients with ICH. A1 astrocytes are closely associated with neuroinflammation and neurotoxicity, whereas A2 astrocytes are neuroprotective. Homer scaffolding protein 1 (Homer1) plays a protective role in ischemic encephalopathy and neurodegenerative diseases. However, the role of Homer1 in ICH-induced inflammation and the effect of Homer1 on the phenotypic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…BBB dysfunction in intracerebral hemorrhage involves glial in the brain. Astrocytic conversion plays a role in the post-inflammatory response of intracerebral hemorrhage ( Fei et al, 2022 ). Astrocyte-related post-inflammation further aggravates BBB leakage and enhances permeability.…”
Section: Bbb Dysfunction In Intracerebral Hemorrhagementioning
confidence: 99%
“…BBB dysfunction in intracerebral hemorrhage involves glial in the brain. Astrocytic conversion plays a role in the post-inflammatory response of intracerebral hemorrhage ( Fei et al, 2022 ). Astrocyte-related post-inflammation further aggravates BBB leakage and enhances permeability.…”
Section: Bbb Dysfunction In Intracerebral Hemorrhagementioning
confidence: 99%
“…H2-D1, C3 and serping1 are markers for the A1 subtype, and pentraxin 3 (PTX3), sphingosine-1-phosphate receptor 3 (S1PR3) and S100 calcium-binding protein A10 (S100A10) are markers for the A2 subtype of reactive astrocytes ( 23 ). Recent research has shown that C3 and serping1 immunoreactivity are the common markers that represent the A1 phenotype, while S100A10 and PTX3 are the common markers of A2 astrocytes ( 24 28 ). Animal research showed that astrocytes were transformed into A1 astrocytes, and A1 astrocytes caused cell death by releasing proinflammatory factors after SAH ( 5 ).…”
Section: Astrocytes Are Involved In the Pathophysiological Process Th...mentioning
confidence: 99%
“…These protrusions, which stretch and fill between the cell bodies of nerve cells and their protrusions, play the role of supporting and separating nerve cells and participate in the blood–brain barrier formation [ 132 , 158 ]. Astrocytes can differentiate into diverse phenotypes under different stimuli, namely, pro-inflammatory type (type A1) and anti-inflammatory one (type A2) [ 159 , 160 , 161 ]. SAH contributes to the transformation of astrocytes into type A1.…”
Section: Tlr4 Expression In Different Cells In the Central Nervous Sy...mentioning
confidence: 99%